Organic Agroedu-Tourism Attractions Toward An Interesting Outdoor Environmental Education To Junior High School Students - Nisa', Ayu Raisa Khairun; Samino, Setijono; Arisoesilaningsih, Endang (Journal of Tropical Life Science, 2014)
The purpose of this study is to evaluate two organic agroedu-tourism attractions developed to 42 students of eight graders of three junior high schools in the village and one school in the city. Organic agroedu-tourism offers two tour programs namely Organic Garden Tour and Organic Farming Technology. Appreciations of the participants were determined by pre and post test after joining the organic agroedu-tourism. The data were analyzed by using descriptive statistics. This study shows that 78.6 % of the participants prefer the Organic Garden Tour and 21.4% find that the Organic Farming Technology is better. Organic agroedu-tourism can improve cognitive aspect of participants from score 1 turned into 3. Most participants had a high interest in joining the organic egroedu-tourism. Organic agroedu-tourism is also able to meet the expectations of participants that are indicated by an increase in the skills and experience of participants from score 2 to 5. Satisfaction of the participants can also be assessed from the high appreciation average before and after joining Organic agroedu-tourism, which are score 4. The appreciation of the participant is shown by their willingness to invite other people to join. Factors affecting participants satisfaction were family background, socio-economy background, personal perception and knowledge. Based on the result, organic agroedu-tourism shows strength to develop the participants understanding, knowledge and skills in integrated organic farming system, even though not all participants are interested to join all programs provided. Farmer groups need to improve the quality of organic agroedu-tourism, for example, completing the facilities and agreed on tourism attractions, enhancing farmers skills as tour guide, providing organic agroedu-tourism program relevant to the school curriculum, and promoting it to public.